2019
DOI: 10.1088/1757-899x/622/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Gadolinium doped Cerium (Ce0,9Gd0,1O1,95) by using Various Carbonates as a Precipitant

Abstract: Gadolinium-doped cerium (Ce0.9Gd0.1O1.95, GDC) as an electrolyte in IT-SOFC has higher performance in nano-sized than the other sized. Carbonate was known as a precipitant agent that could affect the morphology and size of the particle. In this study, the effects of various carbonates as a precipitant agent on the synthesis of GDC by co-precipitation method were investigated. Cerium in the form of Ce(NO3)3.6H2O (cerium nitrate hexahydrate) used in the synthesis process. Three types of carbonates, i.e. ammonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Beside the time, precipitant i. e., potassium carbonate in the precipitation method was also a main factor affecting the physical appearance of the final material [13,30,31] . Many other carbonates were also used as a precipitant in the same co‐precipitation method like sodium hydrogen carbonate [32] . Primarily, K 2 CO 3 was ionized in K + and CO 3 −2 in an aqueous solution, while the Ce 3+ violently reacts with CO 3 −2 ions and the white precipitates were generated immediately, namely Ce (III) basic carbonate (Ce(OH)CO 3 ), which were self‐assembled into bundle‐like structures hierarchically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside the time, precipitant i. e., potassium carbonate in the precipitation method was also a main factor affecting the physical appearance of the final material [13,30,31] . Many other carbonates were also used as a precipitant in the same co‐precipitation method like sodium hydrogen carbonate [32] . Primarily, K 2 CO 3 was ionized in K + and CO 3 −2 in an aqueous solution, while the Ce 3+ violently reacts with CO 3 −2 ions and the white precipitates were generated immediately, namely Ce (III) basic carbonate (Ce(OH)CO 3 ), which were self‐assembled into bundle‐like structures hierarchically.…”
Section: Resultsmentioning
confidence: 99%
“…[13,30,31] Many other carbonates were also used as a precipitant in the same co-precipitation method like sodium hydrogen carbonate. [32] Primarily, K 2 CO 3 was ionized in K + and CO 3 À 2 in an aqueous solution, while the Ce 3 + violently reacts with CO 3 À 2 ions and the white precipitates were generated immediately, namely Ce (III) basic carbonate (Ce(OH)CO 3 ), which were selfassembled into bundle-like structures hierarchically. Afterwards, the Ce(OH)CO 3 precursors were oxidized and decomposed into CeO 2 in air after a specific time (30 mins).…”
Section: Surface Chemical Composition Of Ceo 2 Nanosheetsmentioning
confidence: 99%
“…18 Many researchers synthesized ceria nanomaterials through different methods using various precipitating agents such as ammonium carbonate, and sodium hydrogen carbonate to obtain agglomerated 19 and larger-size particles. 16 Hapsari et al 20 synthesized Gd-CeO 2 using potassium carbonate (K 2 CO 3 ) and potassium hydroxide (KOH) as precipitants and evaluated the effects of K 2 CO 3 on the morphology of CeO 2 . It showed that the morphology of the nanosheets was changed when using K 2 CO 3 as a precipitant.…”
Section: Morphology Of Ms-ceo 2 Andmentioning
confidence: 99%